ANALISIS KEMAMPUAN BERPIKIR KRITIS DAN KEMANDIRIAN BELAJAR SISWA KELAS XI MATERI TURUNAN SELAMA PEMBELAJARAN DARING DENGAN MENGGUNKANA GOOGLE CLASSROOM DAN WHATSAPP - Misfalla Roudlo; Dwijanto Dwijanto (Jurnal Kajian Pembelajaran Matematika, 2021)
The 21st century is a century marked by major transformations. In this century there are many challenges and new demands that call for new breakthroughs. The ability to think critically is an ability needed to face this century. In addition, student learning independence is also needed to be developed. One of the online media that is often used by students and teachers in online learning is google classroom and whatsApp. Based on the results of research conducted on students' critical thinking skills, it was found that 6.67 percent had very high abilities, 40 percent had high abilities, 26.67 percent had moderate abilities, 0 percent had very low abilities and 7 percent of students were very independent, 73 percent independent, 20 percent quite independent, and 0 percent less independent and very less independent in learning. Based on these results, it can be concluded that students 'critical thinking skills during online learning using WhatsApp and Google Classroom derived material can be categorized as high and students' learning independence is categorized as independent.